Primary central nervous system tumors survival in children in ten Colombian cities: a VIGICANCER report - Ramirez, Oscar; Piedrahita, Vivian; Ardila, Jesus; Pardo, Carlos; Cabrera-Bernal, Edgar; Lopera, John; Suarez, Amaranto; Portilla, Carlos Andrés; Narváez, Carlos; Rodriguez, Pamela; Castro, Ximena; Castro, Ángel; et al. (Frontiers in Oncology, 2024)
Primary central nervous system (CNS) tumors are the second most common cancer in children and adolescents, leading to premature death and disability. Population-based survival estimates aid decision-making, but data on survival for primary CNS tumors in Latin America is lacking. We aim to describe survival rates for children treated in ten Colombian cities.We analyzed data from children and adolescents newly diagnosed with cancer between 2012 and 2021, participating in the Childhood Cancer Clinical Outcomes Surveillance System (VIGICANCER) in ten cities in Colombia. VIGICANCER collects clinical outcomes information from twenty-seven pediatric oncology units and conducts active follow-ups every three months. VIGICANCER does not register craniopharyngiomas; we excluded intracranial germ cell tumors for this report. We used the Kaplan-Meier method to estimate the overall survival probability, stratified by sociodemographic variables, topography, WHO malignancy grade, radiotherapy, and surgical resection. We analyzed the variables' prognostic capacity using multivariate proportional Cox's regression, stratified by city and year of diagnosis.During the observation period, VIGICANCER included 989 primary CNS tumors in 879 children and 110 adolescents. The cohort median age was nine; 53% were males, and 8% were Afro-descendants. Most tumors were astrocytic tumors (36%), medulloblastomas